A new office‐based procedure for treatment of snoring: The S.I.Le.N.C.E. study. Issue 1 (22nd January 2020) - Friedman, Michael; Gillespie, M. Boyd; Shabdiz, Faramarz A.; Hiltzik, David H.; Meyer, Ted A.; Ahn, Jeffrey; Catalano, Peter J.; Joseph, Ninos J.
Abstract: Objective: Demonstrate the safety and effectiveness of palatal foreshortening and stiffening in reducing snoring severity in nonobstructive sleep apnea (non‐OSA) patients complaining of chronic disruptive snoring. Methods: In a US‐based 8‐center, open‐label, prospective, single‐arm cohort study, 52 consenting adults with chronic disruptive snoring (snoring impacting a patient's life and causing patient or bed partner to seek medical intervention) were treated via office‐based placement of resorbable, bidirectional, barbed suture implants into the soft palate under local anesthesia. Prior to intervention, home sleep tests (HSTs) were performed to rule out OSA and to document snoring noise level. Both subject and their bed/sleep partners (also consented) completed questionnaires including: bed/sleep partner's scored visual analog scale (VAS) for subjects' snoring severity, and subject scoring for Epworth Sleepiness Scale (ESS) and Pittsburgh Sleep Quality Index (PSQI). Following intervention, HSTs, VAS, ESS and PSQI were repeated at 30, 90 and 180 days. Results: Mean baseline bed/sleep partner VAS was 7.81 ± 1.59. Mean postimplant VAS scores decreased significantly at each measured interval; to 5.77±2.35 ( P  < .001) at 30 days, 4.48 ± 1.81 ( P  < .001) at 90 days, and 5.40 ± 2.28 ( P  < .001) at 180 days. Post treatment improvements in daytime sleepiness and QOL were also observed. Two partial extrusions were reported. No further adverse events were identified. Conclusion: The current study demonstrates the safety and efficacy of the Elevoplasty procedure in reducing snoring severity over a follow‐up period of 6 months. Level of Evidence: 2b